Clinical genetic counselling for familial cancers requires reliable data on familial cancer risks and general action plans. Issue 11 (1st November 2004) - Hemminki, K; Eng, C
Abstract : Familial cancer clustering, without obvious heritability, poses a major challenge for current cancer risk assessment and management. Reliable determination of familial risks for cancer is important for clinical genetic counselling, but medically verified data on familial risks for many malignancies have been limited. However, the nationwide Swedish Family-Cancer Database allows a reliable characterisation of familial risk for all major neoplasms. Even though alert genetic counsellors and certainly clinical cancer geneticists will consider familial cancer clustering in their purview, the standard medical referral systems, which have already been shown to be poor in capturing and referring families at high risk for heritable cancers, are unlikely to ascertain familial aggregations of other cancers that are not known to belong to an inherited cancer syndrome. The data will be helpful in implementing evidence based guidelines for helping the general medical system to ascertain and refer even familial cancer clusters to cancer genetics professionals.